Annals of Dyslexia An Interdisciplinary Journal of the International Dyslexia Association - Gottardo, Alexandra; Chen (Bumgardner), Becky Xi.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Annals of Dyslexia is an interdisciplinary, peer-reviewed journal dedicated to the scientific study of dyslexia, its comorbid conditions; and theory-based practices on remediation, and intervention of dyslexia and related areas of written language disorders including spelling, composing and mathematics. Primary consideration for publication is given to original empirical studies, significant review, and well-documented reports of evidence-based effective practices. Only original papers are considered for publication.
Keywords: Neurology; Philology; Linguistics; Psycholinguistics; Education; Language and Literature; Psycholinguistics; Education, general; Neurology